DESKRPISI PERGERAKAN NILAI CKPN, NPL DAN CAR BANK PASCAPENERAPAN PSAK 71 - Elda Victorya Sinaga; Dimaz Ramananda; Supatmi S (Account : Jurnal Akuntansi, Keuangan dan Perbankan, 2023)
PSAK 71 on Financial Instruments has been in effect since January 1, 2020 and replaces PSAK 55. PSAK 71 regulates several things, one of them is the method of calculating Allowance for Impairment Losses (CKPN). The purpose of this study is to determine the movement of the value of CKPN, CAR and NPL at conventional commercial banks in Indonesia after the implementation of PSAK 71. The results of this study can be concluded as follows, the application of PSAK 71 will increase the value of CKPN at 75 banks and NPL at 44 banks, while the CAR at 57 banks will decrease. The increase in the value of CKPN will reflect the size of the bank's estimate for non-performing productive assets (non-performing loans). The greater the CKPN, the greater the problem of productive assets. The impact of the increase in non-performing loans is a decrease in the CAR value. Overall, the value of CKPN, NPL and CAR will fluctuate, both from ratio movements and changes in ratio movements.